Influence the style of learning to play games by using engineering and mathematics in the development of some Physical abilities, motor and motor control by first-grade primary - Saadi , Hussein; Abdullah , perevan (Journal of Physical Education, 2023)
Her civilized nations childhood roller and directed their attention especially to the belief that Hwlahm the future men and Emad development therefore had to be of interest to that phase and to find methods of modern educational Troy and satisfy the needs of the child motor, cognitive, came to the style of learning to play as an educational treatment are independent of the play activities in the acquisition and expansion horizons of knowledge and aspects of mobility for the child, due to the lack of existing studies to the curricula of special education style learning to play, including includes games, engineering and mathematics, aimed at the development of physical abilities, motor and motor control of children aged (6-7 years) came the current study, an attempt to address that problem. The research aims to the following: - Disclosure on the impact of learning style of playing games by using the (engineering and mathematics) in the development of some physical abilities, motor and motor control by first-grade primary. Detect differences between the learning style of playing games by using the (engineering and mathematics) in the development of some physical abilities, motor and motor control by first-grade primary. Alnmenhj was also used to fit the experimental nature of the research. The research community has been selected in a deliberate from the School of Abu Dhar al-Ghaghara for boys in the portfolio of Nineveh for the academic year (2010-2011), who are (80) pupils, and after exclusion (10) students to conduct commercial reconnaissance them, and (8) of the repeaters and (2) students who have a disability activist, a sample of (60) male students from the first primary school Abu Dhar al-Ghaghara for boys, was a coherence and Altkavo and experience reconnaissance and measurement tribal and sell used curriculum Games engineering and Games Mathematics has been a telemetric been reached to the data after conduct the following statistical methods and eventually reach the researchers to the following: -1 - Has the style of play learning games using sophisticated engineering in physical abilities, motor and motor control with the exception of skill (running a distance of 15 m) of the students of the first experimental group.2 - Made the style of play learning games using the mathematics developed in all physical abilities, motor and motor control in the experimental group II.3 - Physical Education has studied the traditional development in the physical abilities, motor and motor control with the exception of my skills (broad jump and sit from lying down). 4 - Than pupils of the experimental group on the second experimental group in the first test firing in skills (throw the ball soft, oblique lie down, stand on one foot, and snap shooting, kicking). 5 - The experimental group than the second control group in the post test my skills in the objective commentator, kicking, throwing and snap).